2018
DOI: 10.1177/1460458218759699
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in a complex digital media landscape: Pediatric obesity patients’ experiences with online weight, food, and health information

Abstract: This study aimed to explore experiences with online information regarding food, weight management, and health in a group of adolescents in treatment for obesity. Individual semi-structured interviews with 20 adolescents were conducted. Participants used a screen-recorded laptop to demonstrate their search procedures and online information sources. The transcribed interviews were categorized using qualitative content analysis. The adolescents described both encouraging and discouraging experiences. On one hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
0
30
0
3
Order By: Relevance
“…All studies ( table 2 ) were published between 2009 and 2019 and undertaken in Australia 13–15 (n=3), Canada 16–22 (n=7), England 23–31 (n=9), Italy 32 (n=1), the Netherlands 33 (n=1), New Zealand 34 (n=1), Nigeria 35 (n=1), Spain 36 (n=1), Sweden 37 38 (n=2), USA 39–49 (n=11) and Wales 50 (n=1). Studies included CYP with the following LTCs: asthma (n=7), type 1 diabetes (n=5), chronic kidney disease (n=3), cancer (n=3), obesity (n=3), cerebral palsy/spina bifida (n=2), attention deficit hyperactivity disorder (ADHD) (n=2) and HIV, idiopathic scoliosis, colorectal conditions, chronic fatigue syndrome/myalgic encephalitis with n=1 study each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies ( table 2 ) were published between 2009 and 2019 and undertaken in Australia 13–15 (n=3), Canada 16–22 (n=7), England 23–31 (n=9), Italy 32 (n=1), the Netherlands 33 (n=1), New Zealand 34 (n=1), Nigeria 35 (n=1), Spain 36 (n=1), Sweden 37 38 (n=2), USA 39–49 (n=11) and Wales 50 (n=1). Studies included CYP with the following LTCs: asthma (n=7), type 1 diabetes (n=5), chronic kidney disease (n=3), cancer (n=3), obesity (n=3), cerebral palsy/spina bifida (n=2), attention deficit hyperactivity disorder (ADHD) (n=2) and HIV, idiopathic scoliosis, colorectal conditions, chronic fatigue syndrome/myalgic encephalitis with n=1 study each.…”
Section: Resultsmentioning
confidence: 99%
“… 23 26 29 36 38 They also raised concerns about images or content that could be perceived as overly negative or alarmist about their condition, 36 48 although some CYP were concerned about images that they perceived to be unrealistic or idealised (particularly in relation to body image). 37 …”
Section: Resultsmentioning
confidence: 99%
“…Mesmo tendo baixa representatividade nas postagens, os erros propagados por informações não qualificadas comprometem a utilização não organizada das redes sociais nas ações de promoção da saúde. Principalmente, as mídias que permitem informações praticamente em tempo real, como o Instagram, possuem potencial para intervir de maneira tanto benéfica quanto maléfica no bem-estar e na saúde do indivíduo, e por isso, a utilização como ferramenta de intervenção de promoção de saúde, deve ser avaliada com cuidado (HOLMBERG et al, 2018).…”
Section: Categoriasunclassified
“…Current online technologies present a multitude of ways to engage youth in obesity management strategies; these strategies may allow for broader reach compared with traditional in person approaches (Direito A, 2015). Indeed, multiple studies have demonstrated that adolescents are interested in or respond positively to technology-based interventions such as email communications with a health coach and receiving advice/assistance on lifestyle changes via social media (Holmberg C, 2018) (Patrick K, 2014). Indeed, several small studies using social media and online platforms have shown promising results for behavior change and weight loss (Wang Y, 2017).…”
Section: Introductionmentioning
confidence: 99%